Investigasi Digital Forensik pada Perangkat IoT dalam Sistem Rumah Pintar (Smart Home) Menggunakan Framework Application Specific Investigation Model (FASIM) - Deni Koswara; Deni Suprihadi (Universitas Kebangsaan Republik Indonesia, 2024)
The rapid development of the Internet of Things (IoT) presents new opportunities and challenges in cybersecurity, particularly in smart home systems. This study aims to investigate the security and privacy of IoT devices in smart home environments using the Application Specific Investigation Model (FASIM) framework. The research focuses on the processes of acquisition, analysis, and reporting of digital evidence from IoT devices such as light controllers, security cameras, temperature controllers, and door locks. The methods include identifying IoT devices, analyzing data using tools such as Hercules, WireShark, FFMPEG, and Fing, as well as utilizing MD5 hashing to ensure data integrity. The findings reveal that IoT devices in smart home systems can provide valid digital traces that can be further processed in digital forensic investigations. This study is expected to contribute significantly to enhancing the security and privacy of smart home systems and serve as a foundation for future research on digital forensic investigations of IoT devices.